1975
DOI: 10.1002/j.1552-4604.1975.tb01446.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pharmacologic Doses of Steroids on Atrioventricular Conduction in Man

Abstract: His bundle electrograms were performed in ten patients with organic heart disease. Recordings were made at various rates using right atrial pacing. Two grams of methylprednisolone were infused intravenously over a 20-minute period. The PI-A, A-H, H-Q, and H-S intervals were obtained before and up to 1 hour after the infusion of the steroid. The maximum effect was seen at 1 hour. All patients showed a significant prolongation in the A-H interval with negligible effects on other intervals. At the atrial pacing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…At an early stage, CAVB appears to result from AV nodal tissue edema and inflammation that resolves with anti‐inflammatory medication. Dexamethasone is unlikely to directly improve AV conduction, as it has been shown to prolong the A–H (atrium–His) interval in electrophysiological studies12. However, despite the initial success with near‐normalization of the AV conduction time (145 ms at 27 weeks) in the present case, dexamethasone did not prevent the emergence of left atrial and AV nodal fibrosis followed by stepwise deterioration of the AV conduction.…”
Section: Discussioncontrasting
confidence: 63%
“…At an early stage, CAVB appears to result from AV nodal tissue edema and inflammation that resolves with anti‐inflammatory medication. Dexamethasone is unlikely to directly improve AV conduction, as it has been shown to prolong the A–H (atrium–His) interval in electrophysiological studies12. However, despite the initial success with near‐normalization of the AV conduction time (145 ms at 27 weeks) in the present case, dexamethasone did not prevent the emergence of left atrial and AV nodal fibrosis followed by stepwise deterioration of the AV conduction.…”
Section: Discussioncontrasting
confidence: 63%
“…Gould at al. 39 reported that a significant prolongation in the A-H interval was determined after infusion of 2 g of methylprednisolone intravenously over a 20-minute period, and the maximum effect was seen at 1 hour in 10 male subjects. However, all of patients' disease was in an inactive phase, so our patients had been using low doses of oral corticosteroids, but none of them had been taking intravenous therapy.…”
Section: Discussionmentioning
confidence: 99%